Analisis Akurasi Operan Pemain Sepakbola Tim Nasional Indonesia Pada Ajang SEA Games 2021: Babak Kualifikasi Grup: Analysis of the Accuracy of Passing Indonesian National Team Soccer Players at the 2021 SEA Games: Qualification Group Stage - Sendy Mohamad Anugrah (JSKK (Jurnal Sains Keolahragaan dan Kesehatan), 2022)
Pass accuracy is one of the factors that can affect the success of a team in soccer and there is a correlation between the accuracy of the passes and the victory. Therefore, this study aims to determine the total passes and accuracy of passes of Indonesian national team soccer players based on their position when competing in the SEA Games in the group stage. The research method used is quantitative using a descriptive approach to Indonesian National Team soccer players in the 2021 SEA Games group stage. The results show a total of 1601 passes and an accuracy rate of 76.57%. The conclusion of this study is that defenders have more passes than midfielders and forwards and have a higher accuracy of passes than midfielders and forwards. The results of this study are expected to be the basis for further research on match analysis by assessing other technical components in soccer matches.